2017
DOI: 10.1002/ccd.26984
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term outcomes of orbital atherectomy combined with drug‐coated balloon angioplasty for treatment of femoropopliteal disease

Abstract: In this single-center analysis of patients undergoing DCB angioplasty for claudication or CLI, OA was most often used for the treatment of severely calcified lesions. These lesions were more likely to be treated with scoring balloons and less likely to require bailout stenting. At 1 year, target lesion revascularization and primary patency was similar in patients treated with and without adjunctive OA, despite the higher lesion complexity among those receiving the combination procedure. © 2017 Wiley Periodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
0
40
1
Order By: Relevance
“…Our study showed that LA and DCB can decrease the bail‐out stenting rates (32% vs. 57%, p = .008), which is important in FP lesions given the very high rates of stent thrombosis and ISR in such lesions . However, our bail‐out stenting rates were still higher compared to rates reported by RCTs of DCBs for FP ISR .…”
Section: Discussioncontrasting
confidence: 49%
“…Our study showed that LA and DCB can decrease the bail‐out stenting rates (32% vs. 57%, p = .008), which is important in FP lesions given the very high rates of stent thrombosis and ISR in such lesions . However, our bail‐out stenting rates were still higher compared to rates reported by RCTs of DCBs for FP ISR .…”
Section: Discussioncontrasting
confidence: 49%
“…9,46 Previous reports have suggested that the combination of DCB with orbital atherectomy could be a sufficient treatment option for these lesions. 9 The high rate of atherectomy used in our real-world cohort is justified by the belief of our operators that atherectomy devices and, subsequently, optimal vessel preparation, significantly improve DCB outcomes in calcified and complicated (restenosis, CTOs, diffusely diseased) vessels. 9,23 In one prior analysis, Zeller et al showed that the group treated with DCB (± stents as needed) resulted in non-inferior clinical outcomes (freedom from TLR and event free survival) when compared with the stented group for lesions longer than reported by our group.…”
Section: Discussionmentioning
confidence: 99%
“…6 With the evolving use of drug-coated balloons (DCB), these devices are now used in a significant number of endovascular interventions, since they provide improved long-term outcomes compared to PTA, while decreasing the need for permanent scaffold implantation. [7][8][9][10][11] DCB are associated with FP patency rates comparable to primary stenting for the treatment of de novo Adjunctive stent use during endovascular intervention to the femoropopliteal artery with drug coated balloons: Insights from the XLPAD registry FP PAD. 7,8,12 However, in a significant proportion of FP DCB interventions, a vascular scaffold placement may be necessary to treat vessel recoil, significant dissection, or otherwise suboptimal angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…In another similar single-centre trial, the value of orbital atherectomy combined with DCB angioplasty was evaluated for the treatment of calcified femoropopliteal lesions in 89 patients. 35 Despite the higher degree of calcification in patients who underwent atherectomy and DCB compared with those who underwent DCB alone (83% versus 42%; p<0.001), the rate of bailout stenting was lower in the combined therapy group (18% versus 39%; p=0.01). Furthermore, despite more complex lesions in the combined therapy group, patency rates were similar in both.…”
Section: Orbital Atherectomymentioning
confidence: 89%